Coverage and Determinants of Second-Dose Measles Vaccination Among Under-Five Children in Aceh Jaya District, Aceh Province, Indonesia - Maulida, Rizka; Rahmartani, Lhuri Dwianti; Hairani, Lila K; Wahyono, Tri Yunis Miko (Jurnal Epidemiologi Kesehatan Indonesia, 2018)
Indonesia is aiming for measles elimination status by 2020. However, high number of measles cases are still prevalent and there are still coverage differences among provinces. Measles immunization coverage also varies among surveys and routine coverage report. With the addition of second dose measles vaccination (MCV2), measles infections in the country is expected to decrease. However, MCV2 coverage has been low after 2 years of implementation. Aceh Province was chosen for this study because its low coverage. This study aimed to measure the coverage and investigate the determinants of MCV2 in Aceh Jaya, Aceh Province. Dataset from “Assessment of the New 2nd Dose Measles Policy and the School-based Immunization Program in 2 Provinces (Aceh and South Sulawesi)” was used. There were a total of 300 children aged 25 – 37 months with coverage of MCV2 54% in Aceh Jaya District, Aceh Province. After further selection, 129 observations underwent bivariate and multivariate analysis using logistic regression. After controlling all variables, only experience of prompt service at the healthcare provider was associated with child receiving MCV2. We suggest future studies to look more into health care services and willingness to get vaccination. Additionally, with this result we hope the government could improve health care services in their facilities in order to achieve higher coverage.